2015
DOI: 10.4331/wjbc.v6.i4.290
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofMYCgene expression by aberrant Wnt/β-catenin signaling in colorectal cancer

Abstract: The Wnt/β-catenin signaling pathway controls intestinal homeostasis and mutations in components of this pathway are prevalent in human colorectal cancers (CRCs). These mutations lead to inappropriate expression of genes controlled by Wnt responsive DNA elements (WREs). T-cell factor/Lymphoid enhancer factor transcription factors bind WREs and recruit the β-catenin transcriptional co-activator to activate target gene expression. Deregulated expression of the c-MYC proto-oncogene (MYC) by aberrant Wnt/β-catenin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 89 publications
6
103
0
1
Order By: Relevance
“…These increases were also accompanied by a 12-fold to 15-fold increase in the level of c-Myc (Fig. 5d), one of the downstream effectors protein of Wnt/β-catenin signaling [4749]. c-Myc also regulates stemness in CSCs [31].…”
Section: Resultsmentioning
confidence: 99%
“…These increases were also accompanied by a 12-fold to 15-fold increase in the level of c-Myc (Fig. 5d), one of the downstream effectors protein of Wnt/β-catenin signaling [4749]. c-Myc also regulates stemness in CSCs [31].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have reported that PPARD is upregulated in human colorectal adenomas and cancers (Chen et al, 2004;Takami et al, 2007;Dong et al, 2009;Peters et al, 2011;Rennoll and Yochum, 2015). Barak et al (2002) observed a non-statistically significant but reduced expression of PPARD and a decreased incidence of intestinal tumorigenesis in a knockout APC deleted mouse model (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TCF7L2 forms a protein complex with the lymphoid factor 1. Interaction of LEF/TCF with the β-catenin protein results in the formation of a transcription complex that regulates the expression of target genes participating in colorectal carcinogenesis, such as CCND1, PPARD, and c-Myc (He et al, 1999;Krausova and Korinek, 2014;Rennoll and Yochum, 2015). He et al (1999) identified the peroxisome proliferator-activated receptor δ (PPARD) gene as a target of APC through the analysis of global gene expression profiles in human colorectal cancer cell lines (He et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the accumulation and nuclear translocation of β-catenin, where it functions a co-activator of the transcription factor TCF/LEF1516. The Wnt signaling pathway is also responsible for tumor development, particularly in cancers of the digestive system, including hepatocellular, pancreatic, gastric and colorectal cancers17181920. Moreover, Wnt signaling also plays pivotal roles in the tumorigenesis of some other tissue-derived cancers, such as breast cancer and melanoma2122.…”
mentioning
confidence: 99%